ASUHAN KEBIDANAN KEHAMILAN DENGAN PENERAPAN PIJAT DAN RENDAM KAKI DENGAN AIR HANGAT CAMPURAN KENCUR TERHADAP EDEMA KAKI PADA IBU HAMIL - SITI NURHALIMAH (Universitas Aisyah Pringsewu, 2023)
Edema of the legs or swelling of the legs is found in about 80% of pregnant women in the third trimester; this occurs due to uterine pressure, which inhibits venous return, and the pull of gravity, which causes more excellent fluid retention. Edema in pregnancy can be treated through massage therapy. The working principle of massage therapy is to apply direct pressure and focus on the part of the body with edema. This midwifery care aims to provide care for pregnant women by applying massage and soaking the feet with warm water mixed with galingale against leg edema in pregnant women. The midwifery care method used a case study of one pregnant woman with swollen feet. The results of this midwifery care show that leg edema is a common complaint in the third trimester; this is caused by increasing uterine pressure and affecting fluid circulation, with uterine pressure and gravity causing more excellent fluid retention. This therapy helps improve blood circulation by widening blood vessels so that more oxygen is supplied to swollen tissues, so it can be concluded that massage therapy and foot soak with warm water mixed with kencur are safe for pregnant women and are beneficial for reducing swelling.